Directly reprogrammed fragile X syndrome dorsal forebrain precursor cells generate cortical neurons exhibiting impaired neuronal maturation - Edwards, Nicole; Combrinck, Catharina; McCaughey-Chapman, Amy; Connor, Bronwen (Frontiers in Cellular Neuroscience, 2023)
The neurodevelopmental disorder Fragile X syndrome (FXS) is the most common monogenic cause of intellectual disability associated with autism spectrum disorder. Inaccessibility to developing human brain cells is a major barrier to studying FXS. Direct-to-neural precursor reprogramming provides a unique platform to investigate the developmental profile of FXSassociated phenotypes throughout neural precursor and neuron generation, at a temporal resolution not afforded by post-mortem tissue and in a patient-specific context not represented in rodent models. Direct reprogramming also circumvents the protracted culture times and low efficiency of current induced pluripotent stem cell strategies.We have developed a chemically modified mRNA (cmRNA) -based direct reprogramming protocol to generate dorsal forebrain precursors (hiDFPs) from FXS patient-derived fibroblasts, with subsequent differentiation to glutamatergic cortical neurons and astrocytes.We observed differential expression of mature neuronal markers suggesting impaired neuronal development and maturation in FXS-hiDFP-derived neurons compared to controls. FXS-hiDFP-derived cortical neurons exhibited dendritic growth and arborization deficits characterized by reduced neurite length and branching consistent with impaired neuronal maturation. Furthermore, FXS-hiDFP-derived neurons exhibited a significant decrease in the density of pre-and postsynaptic proteins and reduced glutamate-induced calcium activity, suggesting impaired excitatory synapse development and functional maturation. We also observed a reduced yield of FXS-hiDFPderived neurons with a significant increase in FXS-affected astrocytes.Discussion: This study represents the first reported derivation of FXS-affected cortical neurons following direct reprogramming of patient fibroblasts to dorsal forebrain precursors and subsequently neurons that recapitulate the key molecular hallmarks of FXS as it occurs in human tissue. We propose that direct to hiDFP reprogramming provides a unique platform for further study into the pathogenesis of FXS as well as the identification and screening of new drug targets for the treatment of FXS.